The 12 most amazing American cities - Rowell, Rebecca (North Mankato, MN : 12-Story Library, 2015)
Describes twelve major cities in the United States and discusses their history, their most notable landmarks, and other characteristics that make them distinctive.
Includes bibliographical references (page 31) and index.
Keywords: Cities and towns -- United States -- Juvenile literature; Cities and towns; Cities and towns -- United States; United States -- Description and travel -- Juvenile literature; United States -- Description and travel; United States -- Description and travel